Various neuromodulation methods including Deep Brain Stimulation of the medial forebrain bundle combined with psychopharmacotherapy of treatment-resistant depression—Case report - Rymaszewska, Joanna; Wieczorek, Tomasz; Fila-Witecka, Karolina; Smarzewska, Katarzyna; Weiser, Artur; Piotrowski, Patryk; Tabakow, Paweł (Frontiers in Psychiatry, 2023)
Background Treatment-resistant depression remains one of the main concerns of modern psychiatry. Novel methods such as Transcranial Magnetic Stimulation (including deep and theta burst protocols, iTBS) and Deep Brain Stimulation (DBS) can be considered as alternative treatment options. Case presentation Twenty-nine-year-old Caucasian female, single, higher-educated was treated with major depressive disorder initially with standard pharmaco- and psychotherapy. Due to diagnosed treatment resistance additional therapeutic approaches were introduced sequentially: Electroconvulsive therapy (efficient only 4 months) and Transcranial Magnetic Stimulation (intermittent Theta Burst Stimulation, iTBS improved just insomnia). Finally the patient was enrolled to the Deep Brain Stimulation (DBS) study with the medial forebrain bundle target. After 20 months of active DBS a reduction of over 80% of depressive symptom severity was observed (Montgomery-Asberg and Hamilton Depression Rating Scales), together with an 87% reduction of anxiety symptoms intensity (Hamilton Anxiety Rating Scale) and a 90% increase in social and occupational functioning. Subjective assessment of the patient performed with questionnaires and visual analog scales showed less pronounced improvement in terms of depressive and anxiety symptoms, and high reduction of anhedonia. Some mild, transient side effects of neurostimulation were eliminated with an adjustment in stimulation parameters. Conclusions The presented clinical case confirms the possibility of achieving remission after the use of MFB DBS in treatment-resistant depression, but postponed for many months. Nevertheless, personalization of every combined therapy with DBS is necessary with exploration of individual factors as past traumas and personality traits. More reports on long-term observations in DBS treatment in TRD trials (especially focused on MFB target) are needed.